Meta Sintesis Terhadap Mekanisme Partisipasi Publik Pada Kebijakan Yang Berkaitan Dengan Kesejahteraan Sosial di Beberapa Daerah Di Indonesia - Pratiwi, Pratiwi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2013)
The reflection of public interest in policy making is absolutely needed because there is no any system or mechanism to guarantee the apparatus integrity and quality yet. Using qualitative method and meta-systesis analysis, this article has elaborated character of public in Indonesia in public participation, the mechanism and the successful conditions of public participation. Three kinds of research have been used as meta-syntesis objects and this research has concluded that there are seven conditions of successful public participation such us the existence of intellectual organic actor; participation media; media literated society; the role of three other actors such as tecnocrat, bereucrat and public; legal saction, and government guarantee for susceptible groups